Selection of potential microorganism for sago starch fermentation (Biodiversitas Journal of Biological Diversity, 2006)
Fermentation process of sago starch for the production of bioproduct requires potential microorganism that have ability to hydrolyze sago starch. The purpose of this research was to get the potential of amylolytic microorganisms for their capability of amyloglucosidase activity and to know the sugar strains of the fermentation result. Eleven amylolytic microorganisms (9 strains of mold and 2 strains of yeast) were obtained from the collection Research Centre for Biotechnology â€“ Indonesian Institute of Sciences (LIPI), Cibinong-Bogor were used. The selection step was carried out based on their capability of starch hydrolysis to reducing sugar. The best result indicates that the production of reducing sugar reached the highest 18.485 ppm and amyloglucosidase activities was 3.583 units by KTU-1 strain. The highest total acid obtained was 5.85 mg/mL by Rhizopus IFO.R5442. The cell biomass was obtained between 0.5 to 1.74 g dry weight/100 mL and pH of the final fermentation (72 h) were 3.57 to 8.38.Â© 2006 Jurusan Biologi FMIPA UNS SurakartaKey words: sago starch, fermentation, potential microorganism, bioproduct.